Liberalizing the Swiss Meat Market with the EU: Welfare Effects and Impacts on Third Countries - Isabelle Schluep Campo; Robert Jörin (Swiss Journal of Economics and Statistics, 2009)
The paper assesses by means of welfare analysis the effects of trade creation and trade diversion in a Swiss-EU free trade agreement (FTA) in the meat sector and compares it to multilateral trade liberalization. A multi-market multi-region partial equilibrium model is used. The FTA is checked for its conformity with the rules stipulated in Article XXIV of the General Agreement on Tariffs and Trade that prohibits discrimination of third parties. Results indicate that net trade diversion effects are small and do not constitute a long-run impediment to trade. From a trade policy perspective the way is open for an FTA.
Keywords: D60; Q17; Q18; 330; Market access; free trade agreement; trade diversion; partial equilibrium analysis